Living History in the Gödöllő Royal Palace - Dutka, Tímea (Acta Carolus Robertus, 2024)
The study analyzes the practice of costumed guided tours as a form of “living history”, with a special focus on the Royal Palace of Gödöllő. The aim of my research is to explore the practical implementation of living history and its benefits and challenges, as well as to develop suggestions for further improving the palace’s program. I examine the concept of living history from multiple perspectives, including its educational, entertaining, and cultural traditions connections. The study highlights the diversity of living history forms and the significance of different approaches in bringing the past to life. Through an analysis of the programs at the Royal Palace of Gödöllő and the National Museum, I demonstrate how costumed tours and live historical performances can enrich the visitor experience and compare them with other heritage preservation activities. By examining the marketing strategy of experiential walks and the use of social media, I illuminate the challenges and opportunities of promoting the program, emphasizing the importance of online presence. Costumed guided tours at the Royal Palace of Gödöllő bring history to life, thereby deepening visitors’ historical knowledge and increasing interest in local culture. The practice of living history aids in the preservation of cultural heritage and enriches the tourism offer, contributing to the development of the local economy.